2001
DOI: 10.1084/jem.193.8.967
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Course of Experimental Autoimmune Encephalomyelitis and Inflammation Is Controlled by the Expression of Cd40 within the Central Nervous System

Abstract: Although it is clear that the function of CD40 on peripheral hematopoietic cells is pivotal to the development of autoimmunity, the function of CD40 in autoimmune disease outside this compartment is unresolved. In a model of experimental autoimmune encephalomyelitis (EAE), evidence is presented that CD40–CD154 interactions within the central nervous system (CNS) are critical determinants of disease development and progression. Using bone marrow (BM) chimeric mice, the data suggest that the lack of expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
167
1
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(177 citation statements)
references
References 25 publications
6
167
1
3
Order By: Relevance
“…Peripheral macrophages express high levels of CD40 in the CNS during EAE (Figs. 3 and 4) and chimera mice with a CD40 deficiency in the periphery develop mild symptoms of EAE (17). Although infiltrating macrophages express a higher level of activation markers as compared with activated microglial cells (Figs.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Peripheral macrophages express high levels of CD40 in the CNS during EAE (Figs. 3 and 4) and chimera mice with a CD40 deficiency in the periphery develop mild symptoms of EAE (17). Although infiltrating macrophages express a higher level of activation markers as compared with activated microglial cells (Figs.…”
Section: Discussionmentioning
confidence: 95%
“…Although CD40 is implicated in EAE susceptibility, only one study has investigated the role of CD40 expression in the CNS during EAE (17). This study demonstrated that bone marrow (BM) chimera mice with a deficiency in CD40 expression in the CNS, and not in the periphery, exhibited a less severe EAE disease course with reduced numbers of infiltrating macrophages and lymphocytes in the CNS.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Bone marrowderived microglia are known to infiltrate regions suffering from demyelination and remyelination 56 and microglia are responsible for the majority of TNF-a production in the brain in response to immune stimuli. 57 Their presence and activation at demyelination sites would thus be beneficial for the CNS in order to promote remyelination.…”
Section: Bone Marrow-derived Cells and Neurodegenerative Diseasesmentioning
confidence: 99%
“…In fact, the mechanisms of how activation of microglia is regulated have been extensively studied. For example, CD40, a member of the TNF receptor family, has been reported to be involved in microglial activation (5,6). Interactions of CD40 with its ligand (CD154), which is primarily expressed by activated T cells, promote the activation of microglia in the context of enhanced expression of costimulatory molecules and production of proinflammatory cytokines or chemokines and NO (5).…”
mentioning
confidence: 99%